Student's experience in the implementation of Kampus Mengajar 2 (KM2) - Masrina Munawarah Tampubulon; Hafni Nur Insan; Natar fitri Napitupulu; Sakinah Yusro Pohan; Rini Amalia Batubara; Cory Linda Futri; eki Maryo Harahap; Arinil Hidayah (International Journal of Health Science and Technology, 2022)
Program Merdeka Belajar Kampus Merdeka (MBKM) is a program launch by The Minister of Education and Culture which aims to encourage students to master various sciences to prepare them to enter the world of work. Kampus Mengajar is a one of Program Merdeka Belajar Kampus Merdeka (MBKM) which implementation that gives students the right to study for three semesters outside of the study program to improve competencies, both soft skills and hard skills. The objectives of this study are to explore the experiences felt by nursing students in the implementation of the Kampus Mengajar 2 (KM2). The method used in this study is Qualitative Design. Collecting data with Focus Group Discussion (FGD) on 16 informants who attended Kampus Mengajar 2 (KM2). The results of this study are The theme is Information Resources for Campus Teaching Programs, Motivation for Participating in Campus Teaching Programs, Implementation of Campus Teaching Programs, Challenges Faced by Students, Difficulties in Implementing Campus Teaching, Benefits of Campus Teaching, Suggestions From Implementing Kampus Mengajar.